Exploring the Impact of Transformative Leadership and Proactive Personality on Employee Performance: The Mediating Influence of Employee Engagement at PT. Bank BPD DIY Wonosari Branch - Setyo Budi Hadi; Yuni Siswanti; C. Ambar Pujiharjanto (International Journal of Economics, Business and Innovation Research, 2024)
This study discusses the effect of transformational leadership and Proactive personality on employee performance of PT Bank BPD DIY Wonosari branch mediated by Employee Engagement. This research is explanatory research with a survey approach. The population in this study were 104 respondents who were employees of Bank BPD DIY Wonosasi branch. The sampling technique used in sampling is non-probability (saturated sample) which means that the population in this study is entirely used as a sample. The method in this study uses the Structural Equation Modelling (SEM) method. Partial Least Square (PLS) software is used as data processing software to see the relationship formed in the research model. In this study, the results found that transformational leadership and proactive personality directly have a significant and positive effect on the performance of employees of PT Bank BPD DIY Wonosari branch. As for the indirect effect, the results show that transformational leadership and proactive personality have a significant and positive effect on employee performance. Indirectly, transformational leadership and proactive personality indirectly have a significant and positive effect on employee performance mediated by employee engagement of PT Bank BPD DIY Wonosari branch.